Specialised palliative care in nursing homes - Retrospective analysis on the basis of claims data. - Laura Rehner; Kilson Moon; Wolfgang Hoffmann; Neeltje van den Berg (PLoS ONE)
Background The aim of palliative care is to improve the quality of life of patients with a life limiting illness. In Germany, nursing homes are increasingly the last residence and a common place of death for older people. This renders these institutions as places with a high need for palliative care. However, the frequency of specialised palliative care services in nursing homes in Germany is often low. Objectives The aim of this study is 1) to analyse the types and frequencies of services provided by specialised ambulatory palliative care teams in nursing homes in the German federal state of Mecklenburg-Western Pomerania, and 2) to examine whether the frequency of specialised palliative services in nursing homes is comparable to patients living in their private homes. Methods The analysis was based on data of the association of statutory health insurance physicians Mecklenburg-Western Pomerania (Germany), data of the statutory health insurance BARMER, and population data. All patients who received specialised ambulatory palliative care in nursing homes in the years 2015-2017 were included in the analysis. For the comparison of the utilisation of specialised ambulatory palliative care in nursing homes with patients in private households, two comparable groups were created using claims, population data and life-year-mortality tables of the general population. It was assumed that people ≥80 years with a life expectancy of <12 months were potential candidates for the utilisation of palliative care. Data were analysed using descriptive statistics and Chi-Square tests. Results In Mecklenburg-Western Pomerania, 6,096 patients received specialised ambulatory palliative care in the time period 2015 to 2017. Of these, 16.0% (n = 978) were nursing home residents. The median duration of specialised ambulatory palliative care in nursing homes was 12.0 days, for people in private households 27.2 days. The rate of patients receiving specialised ambulatory palliative care in nursing homes was 4.7%, for people in the comparable group in private households it was 9.2% (p < 0.0001). Conclusion Only a small number of nursing home residents received specialised ambulatory palliative care in their last year of life. The rate among those living in their own homes is about twice as high. The results indicate that nursing home residents may have less access to specialised ambulatory palliative care than patients living in private households. Specialised ambulatory palliative care services provision in nursing homes should be improved.